Periodic recurrent fractions of third degree - Zatorsky R.A.; Semenchuk A.V. (Karpatsʹkì Matematičnì Publìkacìï, 2010)
Periodic recurrent fractions of third degreeare investigated by means ofparapermanents of triangular matrices.